The Effects of Temperature and Anesthetic Agents on Ciliary Function in Murine Respiratory Epithelia - Christopher, Adam B.; Ochoa, Sebastian; Krushansky, Evonne; Francis, Richard; Tian, Xin; Zahid, Maliha; Muñoz, Ricardo; Lo, Cecilia W. (Frontiers in Pediatrics, 2014)
Background: Mucus transport mediated by motile cilia in the airway is an important defense mechanism for prevention of respiratory infections. As cilia motility can be depressed by hypothermia or exposure to anesthetics, in this study we investigated the individual and combined effects of dexmedetomidine, fentanyl, and/or isoflurane at physiologic and low temperatures on cilia motility in mouse tracheal airway epithelia. These anesthetic combinations and low temperature conditions are often used in the setting of cardiopulmonary bypass surgery, surgical repair of congenital heart disease and cardiac intensive care. Methods: C57BL/6J mouse tracheal epithelia were excised and cilia dynamics were captured by videomicroscopy following incubation at 15, 22-24, and 37°C with different combinations of therapeutic concentrations of dexmedetomidine (10nM), fentanyl (10nM), and isoflurane (0.01%). Airway ciliary motion was assessed and compared across conditions by measuring ciliary beat frequency (CBF) and ciliary flow velocity. Statistical analysis was carried out using unpaired t-tests, analysis of variance, and multivariate linear regression. Results: There was a linear correlation between cilia motility and temperature. Fentanyl exerted ciliastimulatory effects, while dexmedetomidine and isoflurane each had ciliodepressive effects. When added together, fentanyl+isoflurane, dexmedetomidine+isoflurane, and dexmedetomidine+fentanyl+isoflurane were all ciliainhibitory. In contrast fentanyl+dexmedetomidine did not significantly alter ciliary function. Conclusions: We show ciliary motility is stimulated by fentanyl, but depressed by dexmedetomidine or isoflurane. However, when used in combination, ciliary motility showed changes indicative of complex drug-drug and drug-temperature interactions not predicted by simple summation of their individual effects. Similar studies are needed to examine the human airway epithelia and its response to anesthetics.